Treatment of Canine Pyometra With the Gonadotropin-Releasing Hormone Antagonist Acyline: A Case Series - Batista, Pablo Rodrigo (2015)
To describe the effect of the third-generation gonadotropin-releasing hormone antagonist acyline in the treatment of 4 diestrous bitches with the cystic endometrial hyperplasia-pyometra complex. The 4 bitches were treated with 330. μg/kg of subcutaneous acyline on day 0 and antibiotics, and followed up for 2 weeks. One closed-cervix case showed cervical dilatation 36 hours after treatment, and all the 4 animals showed resolution of clinical signs starting on day 3 posttreatment. Ultrasonographic uterine diameters and luminal contents decreased in the bitches having high progesterone serum concentrations before treatment but not in those with low levels. Serum progesterone importantly decreased from high to basal concentrations in the 3 "ultrasonographically cured" animals. No local or systemic side effects related to the treatment were observed. The gonadotropin-releasing hormone antagonist acyline may have a promising place for the medical treatment of cystic endometrial hyperplasia-pyometra complex in dogs.